2014
DOI: 10.26817/16925777.112
|View full text |Cite
|
Sign up to set email alerts
|

Los Efectos de las Actividades Basadas en Videos en la Comprensión Auditiva de los Estudiantes Iraníes de Inglés Intermedio

Abstract: This study aims at finding the effect of video-based tasks in improving the listening comprehension ability of Iranian pre-intermediate EFL (English Foreign Language) learners. After determining the level of learners, an experimental and control group, each of 20 participants, were nominated to contribute to the study. From the time the pre-test was administered to each group, the experimental group was taught by a course of instruction based on video tasks for teaching listening comprehension. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This is evident as a result of the analysis of the results of the questionnaire. The findings of this study revealed that the perception of first-year Italian language, English language students as well as thirdyear Italian language students, is that the use of video and multimedia materials in the language class will help them improve their listening skills as it is compatible with other previous studies too (Kamilah, 2013;Wottipong, 2014;Sarani et al, 2014;Sulaiman et al, 2017).…”
Section: Conclusion Limitations and Recommendationssupporting
confidence: 85%
“…This is evident as a result of the analysis of the results of the questionnaire. The findings of this study revealed that the perception of first-year Italian language, English language students as well as thirdyear Italian language students, is that the use of video and multimedia materials in the language class will help them improve their listening skills as it is compatible with other previous studies too (Kamilah, 2013;Wottipong, 2014;Sarani et al, 2014;Sulaiman et al, 2017).…”
Section: Conclusion Limitations and Recommendationssupporting
confidence: 85%
“…It is in line with (Sarani et al, 2014), which found that teaching listening by using video showed the students' listening comprehension effectiveness. It improved the students' skill in identifying the topic of the spoken text, making inferences, and finding the specific information in the video.…”
Section: The Average Scoresupporting
confidence: 85%
“…It implies that video podcasts enhance EFL learners' listening comprehension as the resource of learning. (Sarani et al, 2014) also researched using video as media in listening comprehension. The result shows that teaching listening through video-based tasks significantly affected the students' listening comprehension.…”
Section: Page505 Of 514mentioning
confidence: 99%
“…1; February 2021 Published by English Language Education Department of UMG Authors retain copyright and grant the journal right of first publication with the work simultaneously licensed under a Creative Commons Attribution 4.0 International License English Education Program Universitas Muhammadiyah Gresik, East Java, Indonesia and watch but the students will not get bored. Lector, (2013); Sarani et al, (2014) ;Woottipong, (2014) highlighted that students' perception on using video media was positive because by using video media, their listening became better and they were more interested and motivated to learn the skill and the language. This is due to the use of authentic language in the video.…”
Section: Discussionmentioning
confidence: 99%